Avaliação dos ciclos de polimerização da resina acrílica para base de prótese total - Kimpara, Estevão Tomomitsu [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
In the present work it was studied the behavior of four water bath curing cycles of heat activated acrylic resin considered as long duration (I – 65ºC for 30 min;50ºC for 23h and 30min; and 100º C for 1h; II- 50ºC for 24h and the rapid cycle), compared to the known long time curing cycle (9 hours for 72ºC) and short curing cycle (1 h for 65ºC; 30 min to elevate at 100º C and 1:00 to 100º C). Analysis consisted of observations and verification of the residual monomer, weight alterations, dimensional, dimensional lineal, porosity and hardness to determine material performance. The results pointed out that residual monomer presented statistical significant differences in the factor storage and interaction among the factors cycle X storage for weight alteration; statistical significant differences for the factor storage for lineal dimensional alterations, without significant differences for hardness. Porosity was verified in minimum degree in the cycle III and in appreciable amount in the cycle IV

No presente trabalho objetivou-se estudar o desempenho de 4 ciclos de polimerização das RAAT: ciclo I - 65°C por 30 min, 50°C por 23h e 30min e 100°C por 1 h; ciclo II - 50°C por 24h e 1 h a 65°C, 30 min para elevar a 100°C e 1 h a 1 00°C, com outros dois, rotineiramente indicados: ciclo III - 9h a 72°C e o ciclo IV – 1 h a 65°C, 30 min para elevar a 100°C e 1 h a 100°C. As observações, para que pudesse ser analisado o desempenho, foram: verificação do monômero residual, alterações de peso e dimensional linear, porosidade e dureza. Os resultados apontaram quanto ao monômero residual, diferenças significantes estatisticamente no fator ciclo; na alteração de peso, o fator armazenagem e a interação entre os fatores ciclo X armazenagem mostraram diferenças estatisticamente significantes; quanto a alteração dimensional linear, diferenças significantes estatisticamente foram observadas para o fator armazenagem; para a dureza não foram verificadas diferenças significantes e as porosidades não foram observadas nos ciclos I e II, no ciclo III em grau mínimo e em quantidade apreciável no ciclo IV
Keywords: Protese dentaria completa; Resinas dentarias; Polimerização; Monomeros; Monomers